Synthesis, molecular structure, computational study and in vitro anticancer activity of dinuclear thiolato-bridged pentamethylcyclopentadienyl Rh(III) and Ir(III) complexes - Gupta, Gajendra; Garci, Amine; Murray, Benjamin S.; Dyson, Paul J.; Fabre, Gabin; Trouillas, Patrick; Giannini, Federico; Furrer, Julien; Süss-Fink, Georg; Therrien, Bruno (My University, 2013)
Neutral dinuclear dithiolato-bridged pentamethylcyclopentadienyl Rh(III) complexes (C5Me5)2Rh2(?-SR)2Cl2 (R = CH2Ph, 1; R = CH2CH2Ph, 2) and cationic dinuclear trithiolato-bridged pentamethylcyclopentadienyl Rh(III) and Ir(III) complexes [(C5Me5)2M2(?-SR)3]+ (M = Rh, R = CH2Ph, 3; M = Rh, R = CH2CH2Ph, 5; M = Rh, R = CH2C6H4-p-tBu, 7: M = Ir, R = CH2Ph, 4; M = Ir, R = CH2CH2Ph, 6; M = Ir, R = CH2C6H4-p-tBu, 8) were synthesized from the chloro-bridged pentamethylcyclopentadienyl Rh(III) and Ir(III) dimers (C5Me5)2M2(?-Cl)2Cl2 by reaction with the corresponding thiol deriv. (RSH). Complexes 3-8 were isolated as chloride salts. All complexes were obtained in good yield and were fully characterized by spectroscopic methods. The mol. structures of the neutral complexes (1 and 2) show interesting features: the two Rh atoms are bridged by two thiolato ligands with no metal-metal bonds and the pentamethylcyclopentadienyl and chlorido ligands are oriented syn to each other, an uncommon conformation for such dinuclear complexes. These structural features were rationalized using DFT calcns. Addnl., the antiproliferative activity of the complexes was evaluated against the cancerous A2780 (cisplatin sensitive) and A2780cisR (cisplatin resistant) human ovarian cell lines and on the noncancerous HEK293 human embryonic kidney cells. All complexes are active and the cationic Ir complexes 4, 6 and 8 are particularly cytotoxic, with IC50 values in the nanomolar range (IC50 < 0.1 ?M). The catalytic activity of the complexes for the oxidn. of glutathione (GSH) to GSSG was evaluated by NMR spectroscopy. [on SciFinder(R)]
Keywords: anticancer dinuclear thiolato bridged pentamethylcyclopentadienyl rhodium iridium prepn DFT; crystal structure dinuclear thiolato bridged rhodium iridium prepn anticancer; mol structure dinuclear thiolato bridged rhodium iridium prepn anticancer; optimized mol structure dinuclear thiolato bridged rhodium ruthenium energy